The Effects of L-Carnitine, Acetyl-L-Carnitine, and Propionyl-L-Carnitine on Body Mass in Type 2 Diabetes Mellitus Patients - Wang, Dong-Dong; Wang, Tian-Yun; Yang, Yang; He, Su-Mei; Wang, You-Mei (Frontiers in Nutrition, 2021)
Purpose: The study aimed to explore the effects of l-carnitine, acetyl-l-carnitine and propionyl-l-carnitine on body mass in type 2 diabetes mellitus (T2DM) patients. Methods: Randomized controlled trial (RCT) studies of l-carnitine, acetyl-l-carnitine and propionyl-l-carnitine in T2DM patients were searched. The change rates of body mass index (BMI) from baseline values were used as evaluation indicator. The maximal effect (Emax) model by nonlinear mixed effect modeling (NONMEM) was as evaluation method. Results: A total of 10 RCT studies, 1239 T2DM patients were included for analysis, including 8 studies of l-carnitine, 1 study of acetyl-l-carnitine, and 1 study of propionyl-l-carnitine. The study found that l-carnitine could reduce body mass of T2DM patients. Based on the only 1 study each for acetyl-l-carnitine and propionyl-l-carnitine, no significant effects were found in acetyl-l-carnitine or propionyl-l-carnitine. In addition, in order to achieve a plateau of efficacy (80% Emax), 2 g/day l-carnitine was required for at least 2 weeks. Conclusions: 2 g/day l-carnitine was required for at least 2 weeks to affect body mass in T2DM patients, and no significant effects were found in acetyl-l-carnitine or propionyl-l-carnitine.